Are overground or treadmill runners more likely to sustain tibial stress fracture? - Milgrom, C.; Finestone, A.; Segev, S.; Olin, C.; Arndt, T.; Ekenman, I. (British Journal of Sports Medicine, 2003)
Background: Repetitive high bone strain and/or strain rates, such as those that occur during running, contribute to stress fractures as well as promoting maintenance of or increase in bone mass. Kinematic differences are known to exist between overground and treadmill running and these may be reflected in different bone strains and strain rates during the two running techniques.